Synthesis and Antiproliferative Activity of 3 and 7-Styrylcoumarins (2018)
ABSTRACT: A series of styrylcoumarins were obtained via Mizoroki-Heck reactions between 3-bromo-4-methyl-7-(octyloxy)-2H-chromen-2-one or 2-oxo-2H-chromen-7-yl trifluoromethanesulfonate and functionalized styrenes. The structures of the products were elucidated by spectroscopic analysis. All compounds were evaluated against SW480 and CHO-K1 cell lines. A number of hybrids showed good antiproliferative activity. Among the tested compounds, hybrids 6e, 10c and 10d, exhibited the highest activity (IC50- SW480/48h = 6,92; 1,01 and 5,33 μM, respectively) and selectivity (IS48h = >400; 67,8 and 7,2, respectively). In addition, these compounds were able to preserve their activities over time. The results achieved by these hybrids were even better than the lead compounds (coumarin and resveratrol) and the standard drug (5-FU). As regards structure-activity relationship it seems that the location of the styryl group on the coumarin structure and the presence of the hydroxyl group on the phenyl ring were determinant for the activity.